Understanding Spanish Jihadist Terrorism: The Ideology Behind the Metaphors - López, Carlos Yebra (Routledge Critical Terrorism Studies, 2025)
This book offers the first systematic account in English of the Spanish mass press coverage of 'jihadist terrorist' attacks in contemporary Spain.